Popularitas VS Realitas Elektoral: Strategi Komunikasi Digital dalam Pemilu Presiden Indonesia 2024 - Dewi, Risma Amalia Ulfa; Pratiwi, Aprilianti (Jurnal Dinamika Ilmu Komunikasi, 2025)
This study analyzes digital communication strategies in the 2024 Indonesian Presidential Election, focusing on the gap between digital popularity and electoral reality. Using a qualitative descriptive method, this research involved in-depth interviews with three political influencers supporting each candidate pair and one political expert. The findings show that although the Anies-Muhaimin pair dominated digital interactions on Instagram with 45% of conversations, their electoral votes were not proportional to this digital popularity. The study identifies four main digital communication strategies: personal branding, viral momentum, influencer roles, and platform segmentation. However, the effectiveness of these strategies is limited by Indonesian voter characteristics that remain dominated by traditional-emotional patterns, the existence of a silent majority, and structural factors such as money politics, dynastic politics, weak digital campaign regulations, and resource inequality. This research concludes that social media functions more as a space for affirmation rather than political conversion, and digital popularity does not automatically result in electoral victory because it operates within a complex political context.